Sustainable tourism in sport with emphasis on spectators' contribution in environmental preservation - M.S. Kiani (H.S. Skovoroda Kharkiv National Pedagogical University, 2019)
Purpose: examination the sustainable tourism in sport with emphasis on spectators' contribution in environmental preservation. Material and methods. The population of the study consisted of all sports spectators of 27th Fajr Open and Esteghlal vs Tractor rematch from 15th Persian Gulf Pro League. According to Kukran formula sample size was equal to 722 persons. 920 questionnaires distributed among population that 722questionnaires were analyzed .In order to collect data a self-made questionnaire was used which it's validity confirmed by 5 sports teachers of  Razi and Tehran university and variables reliability was calculated  by using Cronbach's alpha coefficient which was equal to 0.89. Data analysis done by using the descriptive and inferential statistics include Kolmogorov-Smirnov, Pearson correlation, path analysis of structural equations, Regression and also AMOS-21 and SPSS-22. The results showed that environmental communication should be formed within the right framework, encourage people to Environmentally Responsible Behavior through a bonus is not necessarily effective and doesn't encourage sports spectator. Results. Result showed that spectators display more cooperation through targeting for enjoyment and are sensitive toward any perceived cost in the implementation of Environmentally Responsible Behavior. The result also showed if cooperation with Environmental Management System doesn't take too much time and totally doesn't interfere with their enjoyment of watching match, they will support it automatically. The results also suggest the need to design efficient equipment to ensure ease of use and as a result reducing the perceived cost associated with Environmentally Responsible Behavior. Conclusion. Sports event owners can encourage spectators to do the Environmentally Responsible Behavior by connecting with them and also induce this fact to spectators that associate with the event can assist them to experience higher quality events in the future.